Encephalopathy with Periodic Discharges In chronic Kidney Disease Patient - Abraham, Miny; Nikhil, Gladson (Nepal Journal of Neuroscience, 2025)
Analysis of spontaneous EEG activity  is an essential method in evaluation of patients with impaired consciousness in both acute care  and chronic settings. It continues to be the only method that allows the bedside monitoring of both immediate  and longterm  cortical functioning associated with the conscious or unconscious state.We report two cases of encephalopathy with periodic discharges in chronic kidney disease patients;